Implementation of Learning With the Mind Maping Method to Improve Student Learning Outcomes in PAI and Ethics Subjects in Junior High School - Furqon, Zenal; Shafwandy Nugraha, Mulyawan (Zona Education Indonesia, 2024)
This study intends to be able to find out the extent to which mind mapping can affect student learning outcomes, especially in PAIBP lessons on prayer pillar material. This research uses quantitative methods with technical tests and non-tests. The object of the study was 13 students of grade VIII SMP Daarut Tauhiid Bandung 2023/2024. Primary data sources are informants (people) who can provide information about research data. The informant in this study was a grade VIII student of SMP Daarut Tauhiid Bandung consisting of 13 female students. In the pre-cycle stage, researchers take data on learning outcomes on the material of the pillars of prayer, subthemes about the division of categories and understanding of each pillar of prayer. At this stage, teachers still use the PBL model with the lecture method in the learning process. The learning outcome data obtained is then used as a comparison of learning outcomes in cycle 1 which applies the mind mapping method to improve student learning outcomes. The results of classroom action research that has been carried out at SMP Daarut Tauhid Bandung in PAIBP subjects with prayer pillar material there are differences in learning outcomes with different methods. With the mind mapping method, students experience a significant improvement in their learning outcomes